Bond behaviour between recycled aggregate concrete and deformed steel bars - Prince, M. John Robert; Singh, Bhupinder (Journal of Structural Engineering, 2024)
The results of thirty pullout tests carried out on 8 mm and 10 mm diameter deformed steel bars concentrically embedded in recycled aggregate concrete designed using equivalent mix proportions with coarse recycled concrete aggregate (RCA) replacement percentages of 0%, 25%, 50%, 75% and 100% are reported towards investigation of bond behaviour of RCA concrete. Bond strengths of the natural aggregate concrete and the RCA concrete was found to be comparable, particularly for the 10 mm rebars, and the RCA replacement percentage had an insignificant effect on peak bond stress values. However, for both the bar sizes, when the measured bond strengths were normalised with the respective compressive strengths, then the relative bond strengths so obtained across all the RCA replacement percentages were higher for the RCA concrete compared to the NCA concrete. Further, higher relative bond strength values were obtained for the 8 mm rebars compared to the 10 mm bars. An empirical bond stress versus slip relationship between RCA concrete and deformed steel bars has been proposed on the basis of regression analysis of the experimental data and it is conservatively suggested that anchorage lengths of 8 mm and 10 mm diameter deformed bars in RCA concrete may be taken the same as in natural aggregate concrete.